Evaluation of fiscal incentives in the Philippines - Danileen Kristel C. Parel (Philippine Institute for Development Studies (PIDS), 2017)
The advantages of foreign direct investment to host countries, particularly on economic growth, have long been recognized. The amount of investment that enters a country is influenced by various factors, including tax rates and the provision of fiscal incentives. This paper (1) assesses how the Philippines fares in attracting investments compared with its neighboring countries and (2) evaluates pending incentive reforms in the country. As the corporate income tax does not take into account other tax rules, effective tax rates, which provide a single measure reflecting the combined effect of all tax rates and incentives, were computed and used in the assessment.
Keywords: 330; Fiscal incentives; tax incentives; foreign direct investment; effective tax rates; tax holiday